The Effectiveness Of Counseling Reality Of Group Settings In Strengthening Students' Self-Regulation To Quit Smoking at SMAN 1 Sungayang - Nari Rati; Masril , Masril; Wahidah Fitriani; Ardimen, Ardimen; Silvianetri, Silvianetri (Cita konsultindo, 2023)
The main problem in this thesis is whether group setting reality counseling is effective in strengthening students' self-regulation to stop smoking at SMAN 1 Sungayang. Due to the heterogeneous background of the students in the area where this high school is located, there is a need for group setting reality counseling in strengthening students' self-regulation to stop smoking. This study used an experimental research type, with a one group pretest and posttest design. In this study the authors provided a group setting reality counseling treatment to 12 students at SMA Negeri 1 Sungayang. The data analysis technique that the authors used in this study was statistical data analysis technique, namely the T test. The results showed that there was a strengthening of students' self-regulation levels after being given reality counseling treatment in group settings and the value of n-gain students' self-regulation levels to stop smoking after getting group setting reality counseling is in the medium category. This provides evidence that there is a significant difference in the level of self-regulation of students to quit smoking after receiving group setting reality counseling interventions. This empirical evidence supports the hypothesis in this study, namely Ho is rejected and Ha is accepted. This means that group setting reality counseling is effective in increasing students' self-regulation to stop smoking at SMAN 1 Sungayang